2014
DOI: 10.1002/pmic.201300418
|View full text |Cite
|
Sign up to set email alerts
|

Development and performance evaluation of an ultralow flow nanoliquid chromatography‐tandem mass spectrometry set‐up

Abstract: LC-MS/MS is the most commonly used technique for the identification and characterization of proteins. The efficiency of the electrospray process is a critical factor in LC-MS/MS. Despite the benefits associated with very low flow rates for the ionization efficiency, most LC-MS/MS platforms are operated at relatively high flow rates. The purpose of this work was to develop a nano LC system operable at a flow rate of 20 nL/min, applicable for routine analysis in proteomics laboratories. Peptide separation was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 44 publications
(54 reference statements)
1
20
0
Order By: Relevance
“…Considering that hMTR4 competes with ALYREF for binding with CBC/RNAs, how do cells ensure specific recruitment of hMTR4 to "export-defective" RNAs, but not export-sufficient RNAs? As previously reported, we found that the protein abundance of ALYREF is~5 times more than that of hMTR4 in HeLa cells (Kocher et al, 2014; Appendix Fig S5). As most of hMTR4 is concentrated in the nucleolus, the nucleoplasmic concentration of hMTR4 must be even less than ALYREF.…”
Section: Discussionsupporting
confidence: 85%
“…Considering that hMTR4 competes with ALYREF for binding with CBC/RNAs, how do cells ensure specific recruitment of hMTR4 to "export-defective" RNAs, but not export-sufficient RNAs? As previously reported, we found that the protein abundance of ALYREF is~5 times more than that of hMTR4 in HeLa cells (Kocher et al, 2014; Appendix Fig S5). As most of hMTR4 is concentrated in the nucleolus, the nucleoplasmic concentration of hMTR4 must be even less than ALYREF.…”
Section: Discussionsupporting
confidence: 85%
“…Many improved and alternative approaches have been introduced in the last years, including capillary electrophoresis (Fonslow & Yates, 2009), superficially porous and sub-micron particles (Blue & Jorgenson, 2015), use of slower flow rates (Köcher et al, 2014), HPLC systems with higher-pressure capabilities ( i.e. , > 20,000 psi) (Shen et al, 2005), and monolithic columns (Iwasaki et al, 2012; Horie et al, 2014; Zhang et al, 2015), among others.…”
Section: In Search Of Better Separationsmentioning
confidence: 99%
“…These two microfluidic techniques have been successfully used for the separation of a large number of compounds including peptides, proteins, enantiomers, drugs, herbicides, pollutants, hormones, estrogens, nutraceuticals, etc. .…”
Section: Introductionmentioning
confidence: 99%